2008
DOI: 10.1248/bpb.31.1639
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Mitochondrial Oxidative Damage and Improved Mitochondrial Efficiency by Administration of Crocetin against Benzo[a]pyrene Induced Experimental Animals

Abstract: The polycyclic aromatic hydrocarbon benzo [a]pyrene (B[a]p), was first isolated from coal tar and characterized by Cook et al. 1) B[a]p is one of the most prevalent environmental carcinogens to which humans are exposed. B [a]p is a very effective carcinogen which interacts with membrane lipids and consequently induces free radical formation.2) B[a]p activates oxidative stress especially lipid peroxidation, which is known to be involved in carcinogenesis.3) B[a]p activates oxidative stress-induces cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
1
22
0
1
Order By: Relevance
“…Na + K + -ATPase is a sodium–potassium pump that is not only involved in the transport of Na + and K + ions across the mitochondrial membrane but also regulates the Ca 2+ concentration in the mitochondria [18]. Failure of the Na + -K + pumps causes the mitochondria to swell up and lyse due to uncontrolled Na + influx and K + efflux [19].…”
Section: Discussionmentioning
confidence: 99%
“…Na + K + -ATPase is a sodium–potassium pump that is not only involved in the transport of Na + and K + ions across the mitochondrial membrane but also regulates the Ca 2+ concentration in the mitochondria [18]. Failure of the Na + -K + pumps causes the mitochondria to swell up and lyse due to uncontrolled Na + influx and K + efflux [19].…”
Section: Discussionmentioning
confidence: 99%
“…ICDH and a-KGDH are the major regulators for the controlling flux in entire TCA cycle. During tumor proliferation impairments in functioning of mitochondrial enzymes such as ICDH, a-KGDH, SDH and MDH leads to alterations causes defection in several steps of TCA cycle [53]. Interestingly analysis the activities of mitochondrial enzymes shows sensitive targets in different pathological status.…”
Section: Discussionmentioning
confidence: 99%
“…Other carotenoids have a recognised protective effect on mitochondria (Wolf et al 2009), and crocin itself has been cited as a mitochondrial protector (Venkatraman et al 2008). Nevertheless, it has been shown that carotenoid breakdown products may exert mitochondriotoxicity, inhibiting mitochondrial respiration, impairing cell redox state and increasing malondialdehyde (Siems et al 2009), and other studies have shown that the carotenoid derivatives retinol and retinoic acid had differential effects in the proliferative and redox status of different cell types (Zanotto-Filho et al 2008).…”
Section: Discussionmentioning
confidence: 99%